The outcome of cyclic feed scarcity on growth and economic limit of commercial feed-based in-door grow-out of Clarias gariepinus (Burchell, 1822) (African Journal of Fisheries Science, 2013)
Growth, feed utilization, and economic limit of commercial pelleted feed use were compared between daily-fed and feed deprived groups of Clarias gariepinus (Burchell, 1822) raised under low density culture. Groups of C. gariepinus were fed daily (Treatment 1) or on alternate days (Treatment 2) for 5½ months, with 45% crude protein commercial pellets. Feeding was at a rate of 6% body weight per day which was considered satiation feeding. Cost and revenue were determined on the basis of feed cost and revenue from fish sales respectively. Treatment 1 yielded profits up to a mean weight of 64±8 g at feed conversion ratio 1.0±0.08 and 4.71% loss at mean weight of 105±10 g and feed conversion ratio (FCR) 2.1±0.7. Treatment 2 was profitable up to harvest mean weight of 264±10 g. Feed conversion ratio, mean weight, and total weight, were significantly higher in Treatment 1 (p